La mediación en la solución de conflictos en las Instituciones que administran el sistema educativo y la tutela del buen vivir - Macías Pérez, Carlos Alberto (2015)
This research had as main objective legal basis for the Law of Arbitration and Mediation . It is intended to cover the institutions that administer the educational system and influence the school mediation process and safeguard the constitutional principle of Good Living in the canton Quevedo. For which was performed to analyze the law Arbitration and Mediation in correspondence with the Constitutional Statement to identify the loophole and promote its reform. The method used in this research has been dialectical , historical and hermeneutic , which allowed information on research and conflict resolution analysis made feasible from a general and particular perspective , the design of the proposal entitled " Reforming the Art. 52 of the Law on Arbitration and Mediation Republic of Ecuador , to include educational institutions of Basic Education of the city of Quevedo , the power to go to a specialized Arbitration and Mediation Center for the resolution of conflicts.